Expression of the Multimeric and Highly Immunogenic Brucella spp. Lumazine Synthase Fused to Bovine Rotavirus VP8d as a Scaffold for Antigen Production in Tobacco Chloroplasts - Alfano, E. Federico; Lentz, Ezequiel M.; Bellido, Demian; Dus Santos, María J.; Goldbaum, Fernando A.; Wigdorovitz, Andrés; Bravo-Almonacid, Fernando F. (Frontiers in Plant Science, 2015)
Lumazine synthase from Brucella spp. (BLS) is a highly immunogenic decameric protein which can accommodate foreign polypeptides or protein domains fused to its N-termini, markedly increasing their immunogenicity. The inner core domain (VP8d) of VP8 spike protein from bovine rotavirus (BRV) is responsible for viral adhesion to sialic acid residues and infection. It also displays neutralizing epitopes, making it a good candidate for vaccination. In this work, the BLS scaffold was assessed for the first time in plants for recombinant vaccine development by N-terminally fusing BLS to VP8d and expressing the resulting fusion (BLSVP8d) in tobacco chloroplasts. Transplastomic plants were obtained and characterized by Southern, northern and western blot. BLSVP8d was highly expressed, representing 40% of total soluble protein (TSP) (4.85 mg/g fresh tissue). BLSVP8d remained soluble and stable during all stages of plant development and even in lyophilized leaves stored at room temperature. Soluble protein extracts from fresh and lyophilized leaves were able to induce specific neutralizing IgY antibodies in a laying hen model. This work presents BLS as an interesting platform for highly immunogenic injectable, or even oral, subunit vaccines. Lyophilization of transplastomic leaves expressing stable antigenic fusions to BLS would further reduce costs and simplify downstream processing, purification and storage, allowing for more practical vaccines.